Feeling/Interpreting: Staging accessible to community in the autistic spectrum. (The Voz a Vos Bulletin, 2026)
The research-creation project in progress The Bull and the Bullfighter: Inquiries, Experimentation, and Reflections on Power Relations in Undergraduate Music Programs in Bogotá, Colombia, developed within the Master’s Program in Artistic Studies, questions the dominator/dominatedpower dynamics present in academia. As a driving element of this reflection, the stage performance Feel/Interpret was created, conceived to engage with audiences within the autism spectrum. The piece narrates the experience of a music student who faces a situation of stage fright during an examination before a teacher trained at a European academy, thereby placing tensions around authority, evaluation, and control at the center of the narrative.The staging articulates acting, lighting design, and sensory elements, using specific colored lights to represent the protagonist’s predominant emotions. This resource aims to facilitate emotional identification and empathy in individuals within the autism spectrum, particularly those who experience difficulties recognizing and understanding others’ emotional states. The presentation also explores the potential of the performing arts as a sensitive and inclusive means of communication with audiences within the autism spectrum, as well as the process through which the performance was conceived. Finally, it presents an analysis of the performances that have taken place and the reception of the work by audiences, reflecting on its impact and scope within the participating community.
Keywords: Power relationships; Musical interpretation; Performing Arts; Autism spectrum.